2006
DOI: 10.1007/s11104-005-3936-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Carboxylates and Acid Phosphatase and Depletion of Different Phosphorus Fractions in the Rhizosphere of a Cereal and Three Grain Legumes

Abstract: This study investigates the distribution of carboxylates and acid phosphatases as well as the depletion of different phosphorus (P) fractions in the rhizosphere of three legume crop species and a cereal, grown in a soil with two different levels of residual P. White lupin (Lupinus albus L.), field pea (Pisum sativum L.), faba bean (Vicia faba L.) and spring wheat (Triticum aestivum L.) were grown in small sand-filled PVC tubes to create a dense root mat against a 38-lm mesh nylon cloth at the bottom, where it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
112
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(137 citation statements)
references
References 59 publications
(40 reference statements)
20
112
1
4
Order By: Relevance
“…Generally, crop plants have various strategies to influence either the spatial or the chemical availability of P in soil. Some plants adapt to low-P soil by changing their root morphology to explore a large soil volume, other excrete P-solubilizing compounds like organic acids, organic and inorganic ions, sugars, vitamins, nucleosides, and enzymes (Staunton and Leprince 1996;Dakora and Phillips 2002;Nurruzzaman et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, crop plants have various strategies to influence either the spatial or the chemical availability of P in soil. Some plants adapt to low-P soil by changing their root morphology to explore a large soil volume, other excrete P-solubilizing compounds like organic acids, organic and inorganic ions, sugars, vitamins, nucleosides, and enzymes (Staunton and Leprince 1996;Dakora and Phillips 2002;Nurruzzaman et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the fungal community in the rhizosphere of legumes and cereals has shown to be different with potential effect in arbuscular mycorrhizal (AM) colonization and P mobilization (Wang et al, 2012). We did not measure these mechanisms; however, in previous studies legumes have shown to have higher organic exudation than wheat (Nuruzzaman et al, 2006;Pearse et al, 2006). Nonetheless, studies comparing root hairs of these crops at field conditions are needed since this trait has been an important mechanism behind crop differences in P acquisition (Gahoonia et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The high P uptake per unit root length shown by pea (2.3 fold) indicates that this crop acquires its P through a mechanism other than root extension. Other mechanisms of P acquisition include higher root exudation, longer root hairs and higher activity and quantity of P transporters (Watt and Evans, 2003;Nuruzzaman et al, 2006;Pearse et al, 2006). In addition, the fungal community in the rhizosphere of legumes and cereals has shown to be different with potential effect in arbuscular mycorrhizal (AM) colonization and P mobilization (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, it was an average sample of the rhizosphere at 0-4 mm from root surfaces. The chosen distance is in accordance with the work of Nuruzzaman et al (2006) who found an increased activity at as far as 3-4 mm from root surfaces. Contrary to that, Dick and Kandeler (2005) highlight that the activity of enzymes is the highest at root surfaces and their closest vicinities (0-1.3 mm).…”
Section: Resultsmentioning
confidence: 86%